Low incidence of colonic complications after severe Shiga toxin-producing E. coli O104:H4 infection - Fründt, Thorben; Leuffert, Julia; Groth, Stefan; Rösch, Thomas; Steurer, Stefan; Lohse, Ansgar W.; Ullrich, Sebastian; Lüth, Stefan (Zeitschrift für Gastroenterologie, 2021)
Background In summer 2011, Shiga toxin producing Escherichia coli (EHEC) serotype O104:H4 caused the most severe EHEC outbreak in Germany to date. The case of a previously recovered patient with symptomatic postinflammatory colonic stenosis following EHEC- infection prompted us to conduct a prospective study to assess the macro- and microscopic intestinal long-term damage in a cohort of patients who had suffered from severe EHEC colitis.Methods Following EHEC infection in 2011, 182 patients were offered to participate in this study between January 2013 and October 2014 as part of the post-inpatient follow-up care at the University Medical Center Hamburg-Eppendorf and to undergo colonoscopy with stepwise biopsies. Prior to colonoscopy, medical history and persistent post-infectious complaints were assessed.Results Out of 182 patients, 22 (12%) participated in the study, 18 (82%) were female. All patients had been hospitalized due severe EHEC enterocolitis: 20 patients (90%) had subsequently developed hemolytic uremic syndrome (HUS), 16 patients (72%) had additionally required dialysis. On assessment prior to colonoscopy, all patients denied any abdominal complaints before EHEC-infection but 8 (36%) patients reported persistent post-infectious symptoms. According to the ROME IV criteria, 4 (18%) patients met the definition for post-infectious irritable bowel syndrome (PI-IBS). In all patients with persistent symptoms, colonoscopies and histological examination were unremarkable. Only in one symptom-free patient, biopsy revealed a locally limited cryptitis of the caecum, while all patients without complaints had inconspicuous histological and endoscopical findings.Conclusion Following infection colonic stenosis is a serious but rare long-term complication in patients who had suffered from severe enterocolitis. However, a significant proportion of these patients develop PI-IBS.
Keywords: EHEC O104:H4; postinfektiöses Reizdarmsyndrom; Kolonstenose; intestinale Langzeitschänden nach EHEC-Infektion